COVID-19 SEIRD AGE-STRUCTURED MODEL WITH LIMITED CAPACITY OF HEALTH FACILITIES AND VACCINATION - Armeina, Diska
It has been more than a year that Covid-19 has become a pandemic with the number of active cases increasing every day. Various actions have been carried out as a form of prevention and intervention of this disease. Vaccination is the most anticipated step because it is considered to be able to increase the body's immunity to suppress Covid-19 cases. However, the limited availability of vaccines requires readiness and strategic steps so that the objectives of vaccination can run effectively. In this study, a multi-group SEIRD model (Susceptible, Exposed, Infected, Recovered, Dead) was used with each compartment divided into 3 age classes, namely 0 - 19, 20 - 59 and> = 60 years and involved parameters of medication, vaccination and contact between age classes. The method used in determining the parameters in the model is by using the nonlinear least square method for Covid data in three provinces in Indonesia, namely West Java, DKI Jakarta and Central Java. The analysis was performed by observing the local and global stability of the disease-free ????0 equilibrium point. Simulations were also carried out to see the sensitivity of the parameters for medication, vaccination and vaccine efficacy.